2006
DOI: 10.1177/156482650602700402
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Deficiency Persists in the Zanzibar Islands of Tanzania

Abstract: Tanzania has, over the past decade, made good progress toward universal salt iodization, but the most recent information and data reported by the World Health Organization (WHO) and UNICEF, and published in the regular "scorecard" of progress by the Network for Sustained Iodine Nutrition (http://206.191.51.240/ Resources_Nutrition.htm), indicates that only 73.8% of households have access to iodized salt. Moreover, only 67% of the accessible salt is satisfactorily iodized to optimal levels. However, Tanzania ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
3
15
1
Order By: Relevance
“…Excessive iodine intakes were observed among people in one or more of four scenarios: first was from those living close to salt factories (Temeke and Kisarawe districts), second scenario to those people living in commercial centres with access to I-salt direct from the factory that has not passed through the steps in the salt marketing chain known to cause iodine loss [ 9 , 34 ] (Temeke and Kisarawe districts in the Dar es Salaam area), and third was in those people living in the Mwanza area, where dried fish products are commonly consumed from Lake Victoria [ 35 ] and preservation was usually with I-salt (Ilemela district). However, despite of the fact that districts with high access to marine/lake seaweeds and fish may have high iodine intake, earlier research in Tanzania has reported inadequate iodine status in other areas with easy access to these foods [ 15 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive iodine intakes were observed among people in one or more of four scenarios: first was from those living close to salt factories (Temeke and Kisarawe districts), second scenario to those people living in commercial centres with access to I-salt direct from the factory that has not passed through the steps in the salt marketing chain known to cause iodine loss [ 9 , 34 ] (Temeke and Kisarawe districts in the Dar es Salaam area), and third was in those people living in the Mwanza area, where dried fish products are commonly consumed from Lake Victoria [ 35 ] and preservation was usually with I-salt (Ilemela district). However, despite of the fact that districts with high access to marine/lake seaweeds and fish may have high iodine intake, earlier research in Tanzania has reported inadequate iodine status in other areas with easy access to these foods [ 15 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spot surveys conducted in the high and low IDD endemic areas in 1999 and 2001 showed great variability in both the process (availability of iodated salt) and impact indicators for iodine deficiency (ID) [ 14 , 15 ]. This paper presents the results from the first national survey in mainland Tanzania, conducted in 2004 to assess the extent of iodated salt use, to measure urinary iodine concentrations (UIC), and to estimate TGP among schoolchildren approximately twelve years after salt iodation was initiated in Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not know whether this actually affects population health (WHO/UNICEF/ICCIDD Consultation Report, 1997), nor the extent to which the performance of these technologies can be improved at a reasonable and sustainable cost. So far, despite the economic constraints they face, Tanzania's salt producers seem to be doing a good job in maintaining a fairly adequate iodine status for the population as a whole (WHO/UNICEF/ICCIDD, 1996;MI, 2001;Lantum et al, 2004;National Bureau of Statistics [Tanzania] and ORC Macro, 2005;Assey et al, 2006a), although this could conceal important variations between population groups or geographic localities (Sundquist et al, 1998;Assey et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Iodine requirements vary by age, and the element is easily supplemented by dietary means given the many years of iodized salt and iodine supplementation in the United States. 3,4 In addition, in neonates and infant patients, iodine is transferred through breast milk, allowing for transfer to this population based on maternal iodine intake. 5 Knowledge of the importance of iodine and preventative campaigns have led to the near extermination of cretinism in the United States and the developed world.…”
mentioning
confidence: 99%